Peningkatan Aktivitas Belajar Siswa SD Negeri 1105 Melalui Model Pembelajaran Active Debate - Lailan Aprina Siregar; Nurhayati Siregar; Parmohonan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The abstract in the English version was written using Calibri-10 pt, and the distance between lines was one space. The abstract contained 150-250 words and only consisted of one paragraph, which contained the objectives or aims, methods, research results, and principal conclusions. The abstract used past tense sentences. The abstract in the English version was written using Calibri-10 pt, and the distance between lines was one space. The abstract contained 150-250 words and only consisted of one paragraph, which contained the objectives or aims, methods, research results, and principal conclusions. The abstract used past tense sentences. The abstract in the English version was written using Calibri-10 pt, and the distance between lines was one space. The abstract contained 150-250 words and only consisted of one paragraph, which contained the objectives or aims, methods, research results, and principal conclusions. The abstract used past tense sentences. The abstract in the English version was written using Calibri-10 pt, and the distance between lines was one space. The abstract contained 150-250 words and only consisted of one paragraph, which contained the objectives or aims, methods, research results, and principal conclusions. The abstract used past tense sentences.